The relationship between sense of community and general well-being of Chinese older adults: A moderated mediation model - Huang, Tingting; Lyu, Houchao; Chen, Xueying; Ren, Jia (Frontiers in Psychology, 2023)
As China becomes an aging society, the impacts of the aging population on the social meso domain, namely, the community level, have received increasing attention in recent years. However, relevant studies are limited. With the assumption that regular community participation positively influences well-being, this study investigated the mediating role of community participation between the sense of community and the general well-being of Chinese older adults and the moderating role of social support. A questionnaire survey was conducted with a valid sample size of 566 participants aged 60 and above in the urban communities of Chongqing, Chengdu, and Zunyi in southwest China. Moderated mediation models were constructed to explore factors related to the well-being of older adults, finding that encouraging community participation can improve the general well-being of older adults and build a better society in Chinese cities. The main findings of this study are as follows: (1) a sense of community significantly and positively relates to community participation and general well-being; (2) community participation partially mediates the relationship between sense of community and general well-being; and (3) each pathway through which sense of community influences older adults’ general well-being is moderated by social support.